CLASSIFICATION OF DEFECTS O F MACROSTRUCTURE OF ROLLER-BEARING STEEL SHH15SG OF RUP “BMZ” PRODUCTION - E. P. Baradjntseva; N. A. Glazunova; I. A. Kovaleva; O. V. Rozhkova (Литьë и металлургия, 2007)
It is shown that the important factor for receiving of high quality of continuously-casted ingot is construction and state of machine equipment of the slug continuous casting.